1992
DOI: 10.1128/jvi.66.3.1674-1681.1992
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of T- and B-cell epitopes of capsid protein of rubella virus by using synthetic peptides

Abstract: A nested set of 11 overlapping synthetic peptides covering the entire sequence of rubella virus capsid protein was synthesized, purified, and tested against human rubella virus-specific T-cell lines and rubella virusseropositive sera. T-cell lines derived from four donors responded strongly to four synthetic peptides containing residues 96 to 123, 119 to 152, 205 to 233, and 255 to 280. Only one peptide (residues 255 to 280) was recognized by all four T-cell lines. Two human immunodominant linear B-cell epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 49 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…We have synthesized 49 synthetic peptides comprising approximately 95% of the amino acid sequences of the structural proteins El (23 peptides), E2 (15 peptides), and C (1 1 peptides) of RV strain M33 (Clarke et a/., 1987) and initiated a series of experiments to search for peptide-specific T cell responses in individuals naturally infected with RV. We have showed that C peptides such as C5 (residues 96-l 23), C6 (residues 119-152), C9 (residues 205-233) or Cl 1 (residues 255-280) can induce significant proliferation of T cells in short-term cultured T cell lines from some RV-seropositive donors (Ou et a/., 1992). The T cell clones used in this study were initially established from the T cell lines of two RV seropositive donors (Ou et a/., 1992).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…We have synthesized 49 synthetic peptides comprising approximately 95% of the amino acid sequences of the structural proteins El (23 peptides), E2 (15 peptides), and C (1 1 peptides) of RV strain M33 (Clarke et a/., 1987) and initiated a series of experiments to search for peptide-specific T cell responses in individuals naturally infected with RV. We have showed that C peptides such as C5 (residues 96-l 23), C6 (residues 119-152), C9 (residues 205-233) or Cl 1 (residues 255-280) can induce significant proliferation of T cells in short-term cultured T cell lines from some RV-seropositive donors (Ou et a/., 1992). The T cell clones used in this study were initially established from the T cell lines of two RV seropositive donors (Ou et a/., 1992).…”
mentioning
confidence: 99%
“…We have showed that C peptides such as C5 (residues 96-l 23), C6 (residues 119-152), C9 (residues 205-233) or Cl 1 (residues 255-280) can induce significant proliferation of T cells in short-term cultured T cell lines from some RV-seropositive donors (Ou et a/., 1992). The T cell clones used in this study were initially established from the T cell lines of two RV seropositive donors (Ou et a/., 1992). A total of 36 clones were isolated by the method a A total of 2 X 1 O4 T cells from each clone was tested for their proliferative response to each synthetrc peptide at a final concentration of 5 pg/ml in the presence of y-irradiated (3000 rad) autologous PBMC 5 X 1 O4 as APC.…”
mentioning
confidence: 99%
See 3 more Smart Citations